Exploring Key Indicators of Community Involvement in Ecotourism Management - UTAMA, I Gusti Bagus Rai; LABA, I Nengah; JUNAEDI, I Wayan Ruspendi; KRISMAWINTARI, Ni Putu Dyah; TURKER, Sidhi Bayu; JULIANA, Juliana (Journal of Environmental Management and Tourism; Vol 12 No 3 (2021): JEMT Volume XII Issue 3(51) Summer 2021, 2021)
This research tries to find key indicators of community involvement in ecotourism management that can ensure that local communities are involved and take part in ecotourism activities must uphold the values of ecotourism, minimize negative impacts; build awareness and appreciation of ecosystems and culture; provide positive opportunities for visitors and hosts; provide direct financial benefits for conservation; provide monetary benefits and empowerment for local residents and increase the hospitality of rural communities. This study uses a desk research method with data and information search techniques online, secondary sources, and other sources of scientific publications. Meanwhile, the analysis technique used is a descriptive qualitative analysis technique, analogy, and comparison of several research results and other scientific publications related to ecotourism management problems. The ecotourism which is directly adjacent to the conservation forest be able to measure the success based on community participation that namely the MOA method which consists of Motivation, Opportunity, and Ability can be used. The ecotourism which is located in the middle of a village or village settlement can be measured by first that ecotourism can integrate nature and tourism so that (1) a unique tourist attraction that is completely different from other types of tourism, (2) optimally maintains nature according to its main function, (3) can encourage the community's economy as a whole, both the community, investors, and local governments, (4) integrating nature and the tourism system to form attractive tourist attractions in the future. The second conclusion is that ecotourism as an opportunity for local workers and attracts government interest (1) can involve local workers as personnel in its operations, (2) attracts government attention to building public facilities, (3) attracts government attention to providing public transportation, terminals, systems passenger safety, information systems. This study uses only a desk research method with data and information search techniques online, secondary sources, and other sources of scientific publications. Key Indicators of Community Involvement in Ecotourism Management for ecotourism which is directly adjacent to the conservation forest, and ecotourism which is located in the village settlement.